Screening and identification of lactic acid bacteria and Allium chinense fermentation by multi-bacterial system - ZHANG Dai, ZHU Li, ZHAO Lingyan, YANG Chunya, NIE Minyu, DENG Fangming (Zhongguo niangzao)
In order to optimize the fermentation process and enhance the quality of fermented Allium chinense, the bacterial diversity and dominant microbiota of traditional natural fermented A. chinense and its fermentation broth was analyzed using high-throughput sequencing. Lactic acid bacteria with excellent acid production, aroma generation, and amino nitrogen production capabilities were screened, the multi-bacterial complex fermentation system was constructed, and their antibacterial effects were investigated. The results showed that Firmicutes was the predominant phylum in traditional fermented A. chinense and its fermentation broth, with Leuconostoc and Lactobacillus as the dominant genera. A total of 25 lactic acid bacteria strains were initially screened, among which strains D1-9, D2-3 and D1 with strong acid production, acetoin production, and amino nitrogen production abilities were selected, respectively. These strains were identified as Lactiplantibacillus plantarum (D1-9), Pediococcus pentosaceus (D2-3), Lactobacillus pentosus (D1). After 24 h of cultivation, the total acidity, acetoin, and amino acid nitrogen contents of strain D1-9, D2-3, D1 reached 18.60 g/L, 47.16 mg/L, and 0.32 g/100 ml, respectively. The three strains had no antagonistic effect and mutualism when cultured together, and had significant antibacterial effect on foodborne pathogenic bacteria. When the mixture culture ratio of strains D1, D1-9 and D2-3 was 1∶1∶2, the fermented A. chinense achieved the highest levels of total acidity (0.92 g/100 g), amino acid nitrogen (0.202 g/100 g), acetoin concentration (52.08 mg/L) and sensory evaluation score (88.40).